Preparation and characterization of graphene oxide-based cation, chelating, and anion exchangers for salt removal - Mahmoud A. Al Azwani; Saleh Al Busafi; El-Said I. El-Shafey (Heliyon)
Due to the shortage of freshwater resources, and the limitations of commonly used ion exchangers, this study aims to prepare, characterize, and test new graphene-based ion exchangers for salt removal. Graphene oxide (GO) was prepared using an oxidative exfoliation method. Using amide coupling, the GO surface was functionalized with taurine to produce a cation exchanger (GOT), and pentaethylenehexamine (PEHA) to produce a chelating ion exchanger (GOP) which was converted to a quaternary ammonium salt (GOQ) which acts as an anion exchanger. The surface area of GO was 220 m2/g, however, decreased tremendously on surface functionalization. X-ray diffraction (XRD) showed that the produced ion exchangers possess amorphous nature. Energy dispersive spectroscopy (EDS) showed the presence of nitrogen in GOP, GOQ, and GOT; and sulfur on GOT. X-ray photon spectroscopy (XPS) showed the presence of -SO3 and S-O on GOT, amine on GOP, and quaternary ammonium group (-NHR2+) on GOQ. TGA shows that GO functionalization is covalent. The produced ion exchangers show an efficient removal of both the cations and anions from the individual salt solution of Ca(NO3)2, MgSO4, and NaCl. GOP sorbs both Ca2+ and Mg2+ via chelation while their anions are sorbed via ion pairing. GOT sorbs the cations via ion exchange while anions are sorbed via ion pairing. GOQ sorbs the anions via electrostatic interaction while the cations are sorbed via ion pairing. Under the experimental conditions in this study, GOP shows the best removal of Ca2+ (80.2 %) and Mg2+ (64 %) while GOT shows the best removal of Na+ (30 %). For anions, GOQ shows the best removal of NO3− (53.5 %), SO42− (84 %), and Cl− (81.8 %). The GO-based ion exchangers seem promising for salt removal from water in addition to being robust at high temperatures and pH.